Pengaruh Pengembangan Produk Terhadap Volume Penjualan pada Kelompok Industri Tas dan Koper Tanggulangin Sidoarjo - artaya, i putu - (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2019)
For a business actor or entrepreneur, plurality of products in the production activities is a key to provide added value to the business undertaken. To create added value requires a breakthrough or continuous innovation in the long term. Through innovation activities, business actors are able to create more new products and be able to increase the fulfillment needs for consumers. This research takes the object of business actor in Intako (bag and luggage industry) area in Tanggulangin Sidoarjo area. From the research results can be seen that there are five things that must be considered business actors in the effort of product development is the bag and suitcase that has been the flagship of Intako Sidoarjo. From the results of the analysis conducted, the results emerged that the three forms of product development that is Initial Development, Improvement Development, and New Use Application results are significant, it means that these three forms of product development worth doing and combined by Intako Sidoarjo in increasing their sales volume.